3D printed structures for optimized carbon capture technology in packed bed columns. Issue 13 (2nd September 2019) - Bolton, Stephen; Kasturi, Abishek; Palko, Scott; Lai, Canhai; Love, Lonnie; Parks, Jim; Xin, Sun; Tsouris, Costas
ABSTRACT: The use of 3D printed structured packing for the optimization of aqueous-amine based carbon capture in packed absorption columns is examined in this paper. An experimental testing system has been set up, and initial comparisons were made between metal, plastic, and 3D printed 16-inch packing elements and between three 8-inch 3D printed elements of different densities. Pressure drop measurements were obtained at various air flowrates under dry conditions. Measurements were also taken for a wet system by adding water at six different liquid flowrates. In each case, theoretical calculations for pressure drop were performed based on a model presented in the literature. It was found that, for the 16-inch dry column, the model slightly overpredicts the pressure drop. The model provides an accurate prediction for the dry 8-inch experimental data, especially for the two least dense packing elements. For the wet system, the model overpredicts the pressure drop, likely due to modeling deficiencies when the column reaches its loading limit. These results provide sufficient confidence to move forward with testing and process intensification of the CO2 capture process.